2022
DOI: 10.3389/fmicb.2022.854172
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Neutrophil-Related Factor LCN2 for Predicting Severity of Patients With Influenza A Virus and SARS-CoV-2 Infection

Abstract: BackgroundInfluenza and COVID-19 are respiratory infectious diseases that are characterized by high contagiousness and high mutation and pose a serious threat to global health. After Influenza A virus (IAV) and SARS-CoV-2 infection, severe cases may develop into acute lung injury. Immune factors act as an important role during infection and inflammation. However, the molecular immune mechanisms still remain unclear. We aimed to explore immune-related host factors and core biomarker for severe infection, to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The Neutrophils_LCN2 cluster was enriched in cytoplasmic translation, neutrophil activation, neutrophil degranulation involved in immune response, ATP metabolic process, and cellular response to interleukin-4. 15 Furthermore, the Neutrophils_LCN2 subset expressed genes related to lung inflammation (including LCN2 and DEFA3), suggesting that they play a role in recruiting neutrophils, inducing pro-inflammatory cytokine signaling, while also promoting anti-inflammatory actions. 16 Additionally, Neutrophils_CAB39L expressed CAB39L, which was mainly associated with substance and energy metabolism, while Neutrophils_ISG15 exhibited a transcriptional signature by expressing interferon-stimulated genes (ISGs), including ISG15, IFIT1, IFIT2, IFIT3, and RSAD2 ( Figures 5 C and S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Neutrophils_LCN2 cluster was enriched in cytoplasmic translation, neutrophil activation, neutrophil degranulation involved in immune response, ATP metabolic process, and cellular response to interleukin-4. 15 Furthermore, the Neutrophils_LCN2 subset expressed genes related to lung inflammation (including LCN2 and DEFA3), suggesting that they play a role in recruiting neutrophils, inducing pro-inflammatory cytokine signaling, while also promoting anti-inflammatory actions. 16 Additionally, Neutrophils_CAB39L expressed CAB39L, which was mainly associated with substance and energy metabolism, while Neutrophils_ISG15 exhibited a transcriptional signature by expressing interferon-stimulated genes (ISGs), including ISG15, IFIT1, IFIT2, IFIT3, and RSAD2 ( Figures 5 C and S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have revealed that LCN2 inhibition or silencing could exert protective effect on LPS-induced ARDS model via inhibition of ferroptosis-related inflammation and oxidative stress ( 23 ). Meanwhile, LCN2 was significantly elevated and positively correlated with disease severity in patients with influenza or COVID-19 ( 24 ). Interestingly, LCN2 expression is markedly upregulated in septic ALI mice compared with those without ALI, which is consistence with our findings ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…LCN2, or Lipocalin-2 (also known as neutrophil gelatinase-associated lipocalin or NGAL), is an acute-phase protein involved in immune response and inflammation [ 57 ]. Recent work has indicated that elevated LCN2 levels are correlated with the severity of COVID-19 infection and may serve as a potential biomarker for disease progression [ 58 ]. Our finding that higher MHCII expression by monocytes is associated with improved prognosis confirms results found in recent studies [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%